Evaluation of holding handheld scanner on muscle activity, heart rate variability, and model accuracy in industrial applications - Ramadan, Mohamed Z.; Nasr, Mustafa M.; Dabwan, Abdulmajeed A.; Khalaf, Tamer M.; Alhaag, Mohammed H.; Soliman, Ahmed T.; Abdelgawad, Abdelaty E. (International journal of industrial ergonomics, 2019)
The capabilities of handheld scanners have been investigated previously in different applications, without considering its impact on the accuracy of model, heart rate variability (HRV), subjective measurements, and worker muscular activity. The present study aims to evaluate the impact of using two handheld scanners, elevation, and orientation of object that is scanned on the basis of aforementioned parameters. To achieve these objectives, electromyographic measurements of six muscles were obtained. Moreover, dependent variables include; NASA task load index (NASA-TLX) as a subjective measure, HRV, and accuracy of the model; while, the scanner-type (laser versus white light scanner), target orientation (0° versus 45°), and elevation (50 cm versus 80 cm table height) were the independent variables. The results of the within-subject design indicated that a light scanner exhibited less accurate performance, lower cardiac cost, less subjective NASA-TLX, and less task execution time than the laser scanner. When using the laser scanner, to reduce muscle contraction and decrease the subjective NASA-TLX, the target elevation and orientation angle with respect to the horizontal plane must be 80 cm and 45°, respectively. However, when using the light scanner, to reduce muscle contraction and the subjective NASA-TLX, the target elevation and orientation angle with respect to the horizontal plane must be 50 cm and 0°, respectively. Furthermore, cardiac rhythms were less stressed when using the laser scanner at a 50 cm target elevation and light scanner at an 80 cm target elevation. •The white light scanner completes the task in less execution time with lower job accuracy. However, the laser scanner completes the task with a long execution time and high job accuracy.•The white light scanner helps worker to scan products in less muscular, cardiac, and subjective (NASA-TELX) activities compared with using the laser scanner.•The lowest deviation of the scanned object (high accuracy) was obtained when the orientation of the scanned part was at an angle of 45° when using the laser scanner and 0° when using the light scanner.•The upper trunk muscles decreased with an increase in the target elevation when using the laser scanner.•In addition, those muscles increased with an increase in the target elevation when using the light scanner.